PENGARUH PERBANDINGAN IKAN KEMBUNG (Rastrelliger kanagurta L.) DAN BIJI NANGKA (Artocarpus heterophyllus) TERHADAP KARAKTERISTIK NUGGET - Amitasya Sinaga, Lucia; Trisna Darmayanti, Luh Putu; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPA, 2020)
This research aims to determine the comparison effect of mackerel with jackfruit seeds on the characteristics of nuggets, and to find out the exact ratio of it’s to produce the best characteristics of fish nuggets. The completely Randomized Design (CRD) was used in this treatment with mackerel and jackfruit seeds ratio as a treatment consist 6 levels : 100%: 0%; 90%: 10%; 80%: 20 ; 70%: 30%; 60%: 40%; 50%: 50%. Each treatment was repeated 3 times to obtain 18 experimental units. The data obtained were analysis ANOVA and if variance nuggets effect to the variables, followed by The Duncan Multiple Range Test (DMRT). The results showed that the comparison of mackerel and jackfruit seeds give a significant effect to the water content, fat content, protein content, carbohydrate content, crude fiber content, hardness, taste (hedonic), texture (hedonic and scoring), and overall acceptance (hedonic). The 50%: 50% ratio of mackerel with jackfruit seeds produces the best characteristics of the product,contain (32,92% water content, ash content 1,90%, fat content 17,63%, protein content 4,65%, carbohydrate content 42,87%, crude fiber content 10,14%) taste liked, aroma liked, texture and overall acceptance liked.